Surface Passivation and Energetic Modification Suppress Nonradiative Recombination in Perovskite Solar Cells - Dong, Wei; Qiao, Wencheng; Xiong, Shaobing; Yang, Jianming; Wang, Xuelu; Ding, Liming; Yao, Yefeng; Bao, Qinye (Nano-Micro Letters, 2022)
Surface passivation via post-treatment is an important strategy for improving power conversion efficiency and operational stability of perovskite solar cells. However, so far the interaction mechanisms between passivating additive and perovskite are not well understood. Here, we report the atomic-scale interaction of surface passivating additive 2,2-difluoroethylammonium bromine (2FEABr) on the MAPbI3. It is found that the bulky 2FEA+ cations tend to distribute at film surface, while the Br− anions diffuse from surface into bulk. A combination of 19F, 207Pb, and 2H solid-state NMR further reveal the Br− anions’ partial substitution for the I− sites, the restricted motion of partial MA+ cations, and the firmed perovskite lattices, which would improve charge transport and stability of the perovskite films. Optical spectroscopy and ultraviolet photoelectron spectroscopy demonstrate that the 2FEABr induced surface passivation and energetic modification suppress the nonradiative recombination loss. These findings enable the efficiency of the p-i-n structured PSC significantly increasing from 19.44 to 21.06%, accompanied by excellent stability. Our work further establishes more knowledge link between passivating additive and PSC performance. Highlights: 1 The partial substitution of Br− on I-sites, and the restricted motion of MA+ cations in correlation with suppressed electron-phonon coupling promote charge transport. 2 The perovskite parent lattice of 2FEABr-treated perovskites was firmed, and the difficulty degree for A-site MA+ cations running out of the inorganic framework was thus enhanced. 3 The efficiency was enhanced from 19.44% to 21.06%, accompanied with excellent stability.